Before, During, and After the First Wave of COVID-19: Mortality Analyses Reveal Relevant Trends in Germany and its States until June 2020 - Morfeld, Peter; Timmermann, Barbara; Groß, J. Valérie; Lewis, Philip; Erren, Thomas C (Das Gesundheitswesen, 2021)
Objective Well-established mortality ratio methodology can contribute to a fuller picture of the SARS-CoV-2/COVID-19 burden of disease by revealing trends and informing mitigation strategies. This work examines respective data from Germany by way of example.Methods Using monthly and weekly all-cause mortality data from January 2016 to June 2020 (published by the German Federal Statistical Institute) for all ages,<65 years and≥65 years, and specified for Germany’s federal states, we explored mortality as sequela of COVID-19. We analysed standardized mortality ratios (SMRs) comparing 2020 with 2016–2019 as reference years with a focus on trend detection.Results In Germany as a whole, elevated mortality in April (most pronounced for Bavaria) declined in May. The states of Hamburg and Bremen had increased SMRs in all months under study. In Mecklenburg-Western Pomerania, decreased SMRs in January turned monotonically to increased SMRs by June. Irrespective of age group, this trend was pronounced and significant.Conclusions Increased SMRs in Hamburg and Bremen must be interpreted with caution because of potential upward distortions due to a “catchment bias”. A pronounced excess mortality in April across Germany was confirmed and a hitherto undetected trend of increasing SMRs for Mecklenburg-Western Pomerania was revealed. To meet the pandemic challenge and to benefit from research based on data collected in standardized ways, national authorities should regularly conduct SMR analyses. For independent analyses, national authorities should also expedite publishing raw mortality and population data, including detailed information on age, sex, and cause of death, in the public domain.
Keywords: SARS-CoV-2/COVID-19; SMR; excess mortality; epidemiology; surveillance